The Influence of Creativity and Self Efficacy on the Performance of Culinary MSMES with Entrepreneurial Orientation As A Mediating Variable(Survey on Culinary MSMES in Surakarta) - Rahadhini, Marjam Desma; Lamidi; Akbar, Abu Bakar (International Journal of Scientific Research and Management (IJSRM), 2025)
The purpose of this study was to analyze the effect of creativity and self efficacy on the performance of culinary MSMEs with entrepreneurial orientation as a mediating variable in culinary MSMEs in Surakarta. The population of this study were 96 owners of culinary MSMEs in Surakarta. The data collection technique used a questionnaire and used accidental sampling techniques. Data analysis techniques using PLS. The validity test uses convergent validity and discriminant validity tests with outer loading> 0.70 and AVE> 0.50. Reliability test using Cronbach's Alpha and CA value> 0.70. Goodness of Fit, NFI, Direct Effect and Indirect Effect in accordance with the required criteria. The results of this study indicate that creativity and self efficacy have a significant effect on entrepreneurial orientation, creativity and self efficacy have a significant effect on MSME performance, entrepreneurial orientation has a significant effect on MSME performance, and entrepreneurial orientation mediates the effect of creativity and self efficacy on the performance of culinary MSMEs in Surakarta.